Japan's poison women female transgression and criminality in the novels of Natsuo Kirino - Rivera, Nicole Yu (College of Arts and Letters, University of the Philippines Diliman, 2015)
This study argues that Natsuo Kirino's three novels - "Real World," "Out," and "Grotesque" - are not noir novels, a label commonly ascribed to them by foreign scholars and readers. Her works can in fact be placed within Japan's literary tradition of writings on female transgression, in particular pre-modern poison woman stories (Dokufu-mono). Further, her works are also reflective of Japanese society's dependence on non-legal mechanisms or social order to address legal crimes and social transgressions alike. The first chapter of this study provides literary and historical context by discussing the development of crime fiction in the West as well as in Japan. In addition, three main characteristics of poison woman stories are identified: pseudo-realistic narratives, socially mobile female characters, and a lack of distinction between legal crimes and social transgressions. In the following chapters, each novel is analyzed with a focus on its similarities to poison woman stories and its depictions of specific non-legal mechanisms of social order. This study conclues that Kirino's novels are similar to poison woman stories in a fourth manner: by depicting gruesome crimes and bleak lives of female criminals, Kirino's novels serve as cautionary tales for Japanese society as a whole, warning society of what is possible if it continues to marginalize women.